Experience with radiopharmacy information system - Jesús Luis Gómez Perales (SpringerOpen, 2022)
Abstract Background The efficient management of hospital radiopharmacy is very important for a good workflow in nuclear medicine and essential to ensure the correct traceability of the radiopharmaceuticals administered to patients. In the hospital radiopharmacy of our nuclear medicine department, it was developed and implemented a radiopharmacy information system (Radiolab). Results From its implementation, important additional functionalities have been added to this software application, according to our requirements and according as well to some of the specific requirements proposed in a recently published consensual tool for validating radiopharmacy software. After more than ten years from the implementation of this software application, it has been analysed its contribution to our hospital radiopharmacy and nuclear medicine department. Conclusions As a result, this radiopharmacy information system provides comprehensive management of our hospital radiopharmacy in an efficient way, and reliable traceability of every dose of radiopharmaceutical administered in our nuclear medicine department.